Dynamic model for controller design of condensate throttling systems. (September 2015) - Hu, Yong; Zeng, De-Liang; Liu, Ji-Zhen; Zhao, Zheng; Li, Ya-zhe
Abstract: Improving the load adjustment rate of coal-fired power plants in China is very important because of grid load fluctuations and the construction of new large-scale power plants connected to the country׳s power grid. In this paper, a new application of condensate throttling system for rapid load adjustment is proposed on the basis of the characteristics of turbine-stored energy. To ensure effective and safe operation of the condensate throttling system, a non-linear control model is derived through reasonable simplifications of fundamental physical laws, and the model parameters are identified using experimental data from a 660 MW supercritical coal-fired power plant. The model outputs are compared with actual measured data for different unit loads. Results show that the established model׳s responses strongly correlate with the actual unit׳s responses and can be used for controller design. Highlights: A new application of condensate throttling system is proposed. A simplified dynamic model of condensate throttling system is given. A combing modelling method is used in the modelling process.